2010
DOI: 10.1155/2010/717591
|View full text |Cite
|
Sign up to set email alerts
|

Visual Performance of Tecnis ZM900 Diffractive Multifocal IOL after 2500 Implants: A 3-Year Followup

Abstract: Purpose. To evaluate visual performance for near, intermediate, and distant vision; complaints of photic phenomena, and patient satisfaction with the new diffractive multifocal IOL used in eyes which underwent phacoemulsification. Methods. Two thousand and five hundred consecutive eyes undergoing Tecnis ZM900 multifocal IOL implantation were included in this retrospective analysis. The minimum followup of 3 months was required after the surgery. Patients were assessed for uncorrected near visual acuity (UNVA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 27 publications
6
21
0
4
Order By: Relevance
“…7 In some models, the incidence of glare and halo have been reported to range from 6% to 40% for glare, and from 11% to 44% for halo. [8][9][10][11] Although, in recent years, the newest multifocal IOLs are typically associated with lower incidence of these phenomenon, [12][13] a recent study of 2500 patients reported that 6.1% of patients treated with Tecnis™ (Abbott Medical Optics Inc., Santa Ana, CA, USA) multifocal IOLs experience glare and 2.1% experience halo. 14 In the present study, the incidence of glare and halo was considerably lower than many previous reports, with a combined incidence of only 6.7%, and no severe incidence reported.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…7 In some models, the incidence of glare and halo have been reported to range from 6% to 40% for glare, and from 11% to 44% for halo. [8][9][10][11] Although, in recent years, the newest multifocal IOLs are typically associated with lower incidence of these phenomenon, [12][13] a recent study of 2500 patients reported that 6.1% of patients treated with Tecnis™ (Abbott Medical Optics Inc., Santa Ana, CA, USA) multifocal IOLs experience glare and 2.1% experience halo. 14 In the present study, the incidence of glare and halo was considerably lower than many previous reports, with a combined incidence of only 6.7%, and no severe incidence reported.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…3 Buna karşılık son yıllardaki yayınlarda yeni konsept multifokal GİL'lerde orta mesafe görme keskinliğinde ve kontrast duyarlılıkta daha iyi sonuçlar bildirmişler, halo ve kamaşma problemlerinde ise azalmalar olduğu tespit edilmektedir. [16][17] 2500 hastaya Tecnis™ (Abbott Medical Optics Inc., Santa Ana, CA, USA) multifokal GİL uygulanmış yeni sayılabilecek bir çalışmada %6,1 hastada kamaşma, %2,1 hastada halo görülmüştür. 16 Bizim çalışmamızda operasyondan 3 ay sonra hiçbir hastada şiddetli halo ve kamaşma şikayeti olmamıştır.…”
Section: Discussionunclassified
“…[16][17] 2500 hastaya Tecnis™ (Abbott Medical Optics Inc., Santa Ana, CA, USA) multifokal GİL uygulanmış yeni sayılabilecek bir çalışmada %6,1 hastada kamaşma, %2,1 hastada halo görülmüştür. 16 Bizim çalışmamızda operasyondan 3 ay sonra hiçbir hastada şiddetli halo ve kamaşma şikayeti olmamıştır. Fotik şikayetlerin azalmasında yeni GİL'in dizaynı çok önemlidir.…”
Section: Discussionunclassified
“…It has an aspheric anterior surface with +4 D near add (+3.0 D at the spectacle plane). A retrospective study on the earlier version of this IOL found an uncorrected distance visual acuity of 20/30 in 85% of eyes and an uncorrected near visual acuity of J1 in 93.7% of 2500 eyes, 3 years postoperatively [35]. Glare and halos were reported as severe by 6.1 and 2.12% of patients, respectively.…”
Section: Advances In Cataract Surgerymentioning
confidence: 97%